Short and Long Term, In Vitro and In Vivo Correlations of Cellular and Tissue Responses to Mesoporous Silicon Nanovectors. Issue 9 (16th December 2012) - Martinez, Jonathan O.; Boada, Christian; Yazdi, Iman K.; Evangelopoulos, Michael; Brown, Brandon S.; Liu, Xuewu; Ferrari, Mauro; Tasciotti, Ennio
Abstract The characterization of nanomaterials and their influence on and interactions with the biology of cells and tissues are still partially unknown. Multistage nanovectors based on mesoporous silicon have been extensively studied for drug delivery, thermal heating, and improved diagnostic imaging. Here, the short‐ and long‐term changes occurring in human cells upon the internalization of mesoporous silicon nanovectors (MSV) are analyzed. Using qualitative and quantitative techniques as well as in vitro and in vivo biochemical, cellular, and functional assays, it is demonstrated that MSV do not cause any significant acute or chronic effects on cells and tissues. In vitro cell toxicity and viability are analyzed, as well as the maintenance of cell phase cycling and the architecture upon the internalization of MSV. In addition, it is evaluated whether MSV produce any pro‐inflammatory responses and its biocompatibility in vivo is studied. The biodistribution of MSV is followed using longitudinal in vivo imaging and organ accumulation is assessed using quantitative elemental and fluorescent techniques. Finally, a thorough pathological analysis of collected tissues demonstrates a mild transient systemic response in the liver that dissipates upon the clearance of particles. It is proposed that future endeavors aimed at understanding the toxicology of naked drug carriers should be designed to address their impact using in vitro and in vivo short‐ and long‐term evaluations of systemic response.